Enhanced photovoltaic conversion efficiency in bulk heterojunction solar cells upon incorporating nanohybridized PbS quantum dots/multiwall carbon nanotubes. Issue 1 (17th January 2014) - Baral, Jayanta Kumar; Sharma, Ankit; Wang, Defa; Ma, Dongling; Truong, Vo-Van; Izquierdo, Ricardo
<x content-type="archive" xml:space="preserve">Abstract</x> We report on a modified bulk heterojunction (BHJ) solar cell in which a nanohybridized composition of lead sulfide (PbS) colloidal quantum dots (QDs) and multiwall carbon nanotubes (MWCNTs) were incorporated into a standard regioregular poly(3-hexylthiophene) (rr-P3HT):phenyl-C61-butyric acid methyl ester (PCBM) blend. This hybrid ((P3HT:PCBM):PbS-QD/MWCNT) solar cell exhibits an increased power conversion efficiency (PCE) of 3.40% as compared to that of 2.57% from a controlled P3HT:PCBM standard BHJ solar cell fabricated under similar experimental conditions. The 32% increase in efficiency is effectively attributed to the extended quantum-dot-sensitization in the near-infrared (NIR) due to the absorbance of QDs/CNTs in the spectral range from 700 nm to 1450 nm. The strong conjugation, controlled coupling and nanohybridization of QDs/CNTs played an important role towards the improvement of PCE since it is proposed that excitons generated in the QDs can be efficiently dissociated at the QD/CNT interface by transferring the electrons to the CNTs followed by holes transfer to the P3HT. In this ternary blend, the staggered energy band alignment between P3HT and the QDs allows both electrons and holes transfer from the QDs to the PCBM and the P3HT, respectively. Subsequently, the dissociated carriers have been efficiently transported by the CNTs and P3HT to favorable respective electrodes.